Pendugaan Potensi Tumbuhan Berkayu di Sekitar Fakultas Kehutanan dan Lingkungan Universitas Kuningan - Jaya, Ramdhan Risnur; Supartono, Toto; Hendrayana, Yayan (Fakultas Kehutanan dan Lingkungan, Universitas Kuningan, 2024)
Forest potential is characterized by vegetation diversity because it is the most dominant resource from the forest component. The presence of community wood plantations in private forests and community land can provide a positive role both economically and ecologically. Types of local wood such as White Teak, Sengon, Jabon, Acacia, Mahogany and others. These types have been cultivated by farmers for a long time and are managed traditionally. It's just that the potential amount of wood contributed from woody plants is not yet known for certain. In fact, data on wood potential is needed to provide information on wood availability to communities where the wood supply is not enough to meet their needs, especially if they only rely on natural forests. If potential information is known, the government can take policies regarding the development of woody plants, especially from mixed gardens. On this basis, research was conducted on Estimating Timber Potential in the Faculty of Forestry and Environment, Kuningan University Potensi hutan dicirikan oleh keanekaragaman vegetasi karena merupakan sumber daya yang paling dominan dari komponen hutan. Kehadiran hutan tanaman rakyat di hutan milik dan lahan masyarakat dapat memberikan peran positif baik secara ekonomi maupun ekologis. Jenis kayu lokal seperti Jati Putih, Sengon, Jabon, Akasia, Mahoni dan lain-lain. Jenis ini sudah lama dibudidayakan oleh petani dan dikelola secara tradisional. Hanya saja potensi kontribusi kayu dari tanaman berkayu belum diketahui secara pasti. Padahal, data potensi kayu diperlukan untuk memberikan informasi ketersediaan kayu kepada masyarakat yang pasokan kayunya tidak cukup untuk memenuhi kebutuhannya, apalagi jika hanya mengandalkan hutan alam. Jika diketahui informasi potensinya, pemerintah dapat mengambil kebijakan terkait pengembangan tanaman berkayu, khususnya yang berasal dari kebun campuran. Atas dasar itulah dilakukan penelitian Pendugaan Potensi Kayu di Fakultas Kehutanan dan Lingkungan Hidup Universitas Kuningan